2021
DOI: 10.1111/vde.13037
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of long‐term oclacitinib maleate therapy in dogs with atopic dermatitis

Abstract: Background -Canine atopic dermatitis (cAD) is a chronic disease characterised by hypersensitivity to environmental allergens. Oclacitinib maleate selectively inhibits pro-inflammatory mediators associated with cAD. However, the impact of chronic oclacitinib use on immunocompetence requires further investigation.Objectives -Herein, we examined the potential immunomodulatory effects of prolonged oclacitinib treatment in dogs.Animals -Thirteen privately owned dogs with cAD, treated with 0.4-0.6 mg/kg oclacitinib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 31 publications
(66 reference statements)
3
15
0
Order By: Relevance
“…A single in vitro study showed no effect on cytokine production with oclacitinib at therapeutical concentration for canine AD 38 . A 12 months in vivo study with oclacitinib in atopic dogs showed no effect on the numbers of CD4+IL‐4+ and CD4+IFN‐β+ cells 37 . With oclacitinib preferably inhibiting JAK1, it could be theorised that the previously shown lack of effect on IL‐4 (signalling via JAK1 and JAK3) and IFN‐ (signalling via JAK1 and JAK2) production also could be extrapolated to IL‐2 (signalling via JAK1 and JAK3) and IL‐10 production (signalling via JAK1 and TYK2) 36 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…A single in vitro study showed no effect on cytokine production with oclacitinib at therapeutical concentration for canine AD 38 . A 12 months in vivo study with oclacitinib in atopic dogs showed no effect on the numbers of CD4+IL‐4+ and CD4+IFN‐β+ cells 37 . With oclacitinib preferably inhibiting JAK1, it could be theorised that the previously shown lack of effect on IL‐4 (signalling via JAK1 and JAK3) and IFN‐ (signalling via JAK1 and JAK2) production also could be extrapolated to IL‐2 (signalling via JAK1 and JAK3) and IL‐10 production (signalling via JAK1 and TYK2) 36 .…”
Section: Discussionmentioning
confidence: 94%
“…In dogs, two recent in vivo studies showed a reduction between pre‐ and post‐treatment percentages of Treg cells in dogs receiving an 8 day (20 mg/kg/day) and a 90 day (5 mg/kg/day) course of CSA, respectively 34,35 . These changes were, however, not statistically significant 36,37 . Suppressive effects of CSA on T‐cell proliferation and IL‐10 production in dogs were shown in vitro and in vivo, 38,39 although the in vivo study was performed only with high dosages (20 mg/kg/day) of CSA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Banovic et al [ 134 ] have reported an immunosuppressive effect of oclacitinib in dogs when used at a dose higher than that used in the treatment of allergic pruritus. However, an increase in CD4+ lymphocyte populations in dogs was observed after long-term treatment with oclacitinib [ 135 ].…”
Section: Introductionmentioning
confidence: 99%